Understanding responses to gait instability from plantar pressure measurement and the relationship to balance and mobility in lower-limb amputees. (February 2016) - Howcroft, Jennifer; Lemaire, Edward D.; Kofman, Jonathan; Kendell, Cynthia
Abstract: Background: Measuring responses to a more unstable walking environment at the point-of-care may reveal clinically relevant strategies, particularly for rehabilitation. This study determined if temporal measures, center of pressure-derived measures, and force impulse measures can quantify responses to surface instability and correlate with clinical balance and mobility measures. Methods: Thirty-one unilateral amputees, 11 transfemoral and 20 transtibial, walked on level and soft ground while wearing pressure-sensing insoles. Foot-strike and foot-off center of pressure, center of pressure path, temporal, and force impulse variables were derived from F-Scan pressure-sensing insoles. Findings: Significant differences ( P < 0.05) between level and soft ground were found for temporal and center of pressure path measures. Twenty regression models (R 2 ≤ 0.840), which related plantar-pressure-derived measures with clinical scores, consisted of nine variables. Stride time was in eight models; posterior deviations per stride in six models; mean CoP path velocity in five models; and anterior–posterior center of pressure path coefficient of variation, percent double-support time, and percent stance in four models. Interpretation: Center of pressure-derived parameters, particularly temporal and center of pressure path measures, can differentiate between level and soft ground walking for transfemoral and transtibial amputees. Center of pressure-derived parameters correlated with clinical measures of mobility and balance, explaining up to 84.0% of the variability. The number of posterior deviations per stride, mean CoP path velocity stride time, anterior–posterior center of pressure path coefficient of variation, percent double-support time, and percent stance were frequently related to clinical balance and mobility measures. Highlights: Center of pressure measures discern between gait conditions for lower-limb amputees. Temporal and center of pressure measures discriminate between gait conditions. Center of pressure measures relate to clinical balance and mobility measures. Intact limb measures are highly relevant to balance and mobility.